Creating Pores on Graphene Platelets by Low‐Temperature KOH Activation for Enhanced Electrochemical Performance. Issue 17 (8th March 2016) - Wu, Shuilin; Chen, Guanxiong; Kim, Na Yeon; Ni, Kun; Zeng, Wencong; Zhao, Yuan; Tao, Zhuchen; Ji, Hengxing; Lee, Zonghoon; Zhu, Yanwu
Abstract : KOH activation of microwave exfoliated graphite oxide (MEGO) is investigated in detail at temperatures of 450–550 °C. Out of the activation temperature range conventionally used for the preparation of activated carbons (>600 °C), the reaction between KOH and MEGO platelets at relatively low temperatures allows one to trace the structural transition from quasi‐two‐dimensional graphene platelets to three‐dimensional porous carbon. In addition, it is found that nanometer‐sized pores are created in the graphene platelets at the activation temperature of around 450 °C, leading to a carbon that maintains the platelet‐like morphology, yet with a specific surface area much higher than MEGO (e.g., increased from 156 to 937 m 2 g –1 ). Such a porous yet highly conducting carbon shows a largely enhanced electrochemical activity and thus improved electrochemical performance when being used as electrodes in supercapacitors. A specific capacitance of 265 F g –1 (185 F cm –3 ) is obtained at a current density of 1 A g –1 in 6 m KOH electrolyte, which remains 223 F g –1 (156 F cm –3 ) at the current density of 10 A g –1 . Abstract : The structural transition from quasi‐two‐dimensional (2D) graphene platelets to three‐dimensional (3D) porous carbon is traced by performing the KOH activation of graphene under mild conditions. An etching in graphene platelets occurred at low temperatures, which creates planar pores in graphene, leading to enhanced electrochemical performance due to the pseudocapacitance at the edges or defects.